2014
DOI: 10.1007/s00595-014-0967-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision totally extraperitoneal inguinal hernia repair: our initial 100 cases and comparison with conventional three-port laparoscopic totally extraperitoneal inguinal hernia repair

Abstract: SILS-TEP repair seems to be safe and feasible, with no significant differences in the total medical charges for the hospital stay or the postoperative pain score 3 months after surgery compared with conventional three-port TEP repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…Some reports showed comparable postoperative pain, and other reports didn't mention about pain between two groups. 1,5,6,10 In our study and some other researchers described that patients suffered more pain on immediate postoperative day. 1,3 In our SUTI-TEP experience of using many different kinds of SILS port including home-made glove port, it seemed that patients suffered more immediate postoperative pain after SILS than after conventional multi-port surgery (data not shown).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Some reports showed comparable postoperative pain, and other reports didn't mention about pain between two groups. 1,5,6,10 In our study and some other researchers described that patients suffered more pain on immediate postoperative day. 1,3 In our SUTI-TEP experience of using many different kinds of SILS port including home-made glove port, it seemed that patients suffered more immediate postoperative pain after SILS than after conventional multi-port surgery (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…4 The safety and feasibility outcome results from a current study, which is designed to compare SUTI-TEP and C-TEP procedures, have shown no differences in length of hospital stay, POD 7 th pain VAS score, postoperative complications, and chronic pain just like as demonstrated by other papers. 5,6 No recurrence was noted during follow up (5~36 months) in both groups.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Since then, it has become widespread and has resulted in less postoperative pain, faster recovery, and lower recurrence rates. Currently, single-incision laparoscopic surgery (SILS) is considered to achieve better cosmetic outcomes than conventional laparoscopic surgery [1]. In general, previous lower abdominal surgery (PLAS) is considered to be a relative contraindication to endoscopic repair for inguinal hernia.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has led to trials of single incision techniques for both the transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) approaches [2,[4][5][6][7]. However, single incision laparoscopic surgery (SILS) has met with some resistance because of limitations including the difficult ergonomics of single incision instruments, the reported increase in port-site herniation following SILS, and the relatively steep learning curve [8][9][10].…”
Section: Introductionmentioning
confidence: 99%